Laccase activity as an indicator of peat degrading microbes in several types of peatlands use in West Sumatra, Indonesia - Hijri, Nurul; Naspendra, Zuldadan; Harianti, Mimien; Budi Prasetyo, Teguh (Talenta Publisher, 2022)
Land clearing and drainage activities on peatlands had boosted the decomposition rate of organic matter, caused by an increase in soil temperature and soil microbial activity. Enzyme activity is a sensitive indicator to measure changes in the decomposition process. The enzyme activity associated with the decomposition of organic matter is Laccase. This research aimed to study Laccase as an indicator of lignin degradation in several types of peatland use in Pesisir Selatan, West Sumatra, namely forests, shrubs, oil palm plantations, agricultural land, and bare land. The Laccase activity was measured by using the ABTS method. The results of our study show that Laccase activity in several types of peatland use from the highest to the lowest follows the order: agricultural land (LP) 3.20 Î¼g.g-1.hour-1 > bare land (LT) 1.46 Î¼g.g-1.hour-1 > shrub (SB) 1.17 Î¼g.g-1.hour-1 > smallholder oil palm plantation (PSr) 0.66 Î¼g.g-1.hour-1 > private company oil palm plantation (PSs) 0.70 Î¼g.g-1.hour-1 > forest (H) 0.06 Î¼g.g-1.hour-1. Soil characteristics that affect the enzyme activity are water content, which is negatively correlated with the Laccase enzyme. The higher the water content in the peat material, the lower the Laccase activity. Therefore, it is necessary to control the soil water content high to prevent the rate of peat decomposition. Keywords: Laccase, enzyme, oil palm plantation, land use, peatland.